Multiparasitism enables a specialist endoparasitoid to complete parasitism in an unsuitable host caterpillar - Kazumu Kuramitsu; Yooichi Kainoh; Kotaro Konno (Scientific Reports)
Abstract Parasitoid wasps serve as natural enemies of numerous insect species; therefore, knowledge of host-parasitoid interactions is fundamental for understanding ecosystems. Each endoparasitoid wasp taxon exhibits a specific host range. Female parasitoids, however, occasionally oviposit into non-host species. Since the survival probability of eggs in non-host species is virtually zero, these behaviors have long been considered maladaptive. However, in the present study, we found that eggs of a specialist parasitoid, Cotesia kariyai (Hymenoptera: Braconidae), oviposited in unsuitable host caterpillars, Mythimna loreyi (Lepidoptera: Noctuidae), successfully complete larval development in the non-host when these caterpillars are simultaneously oviposited by another naturally sympatric parasitoid wasp, Meteorus pulchricornis (Hymenoptera: Braconidae), for which My. loreyi is the usual host. This observation suggests that the seemingly maladaptive behavior of ovipositing in unsuitable host insects can be adaptive, allowing them to maintain reproductive potential in environments where their ordinary hosts are absent. We propose a new term, “pirate parasitism”, for this type of obligatory multiparasitism. Understanding detailed mechanisms of this phenomenon may provide deeper insights into parasitoid-host dynamics and evolution of host use strategies by parasitoids.